Diverticulitis‐induced pylephlebitis possibly misdiagnosed as biliary duct obstruction. Issue 4 (3rd May 2016) - Kashiura, Masahiro; Sugiyama, Kazuhiro; Akashi, Akiko; Hamabe, Yuichi
Abstract : Case: A 59‐year‐old Asian man presented to our emergency department with hypogastrium pain, loss of appetite, and diarrhea. On admission, he was hypotensive and jaundiced. Laboratory test results revealed thrombocytopenia, hypercreatininemia, and hyperbilirubinemia. Color Doppler sonography showed no blood flow in the right and left branches of the portal vein, which seemed similar to biliary obstruction. Enhanced computed tomography showed portal vein thrombi, consistent with pylephlebitis; a broad‐spectrum antibiotic and an anticoagulant were administered. Outcome: The patient died of multiple organ failure 22 h post‐admission. An autopsy revealed suppurative thrombi in the portal vein, multiple liver abscesses, and diverticulitis in the sigmoid colon. Conclusion: Pylephlebitis, a rare complication of intra‐abdominal infections, is associated with high rates of morbidity and mortality. Ultrasonography findings mimic those of biliary obstruction. Enhanced computed tomography is useful for diagnosing this condition.